PENERAPAN TATA KELOLA DALAM PENINGKATAN MUTU TPA NUR JANNAH - Pujianto, Pujianto; Pratiwi, Lily Indah; Halik, Bachtiar Rahman (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Technological developments and changes in lifestyle have resulted in several changes, one of which is the role of parents in parenting children. Currently, many parents who should be the main educators in their children's growth and development are now working and their role as educators is being replaced by child care workers. The service partners this time are TPA and KB Nur Jannah (Daycare) which are located on Jl. Sememi Jaya Selatan, Kec. Sememi, Surabaya City. TPA Nur Jannah has been present since 2012 and KB Nur Jannah since 2014. PPM objectives: (1) partners can prepare appropriate financial reports (2) improve the quality of facilities and infrastructure. Based on these objectives, the problem aspects faced by partners are financial and infrastructure aspects. Regarding financial aspects, partners record regularly and are still simple, so training is needed in making simple financial reports. In terms of facilities and infrastructure, partners still lack playmates, beds and potties for children's comfort facilities, so there is a need for additional facilities and infrastructure to support children's comfort and safety. Based on the problems faced by partners, the solution offered is (1) partners can prepare good financial report records and it is hoped that partner records will increase by 40% (2) there will be an increase in infrastructure by adding folding mattresses, playmates and potties